Experimental Arterial Thrombosis in Rats with Continuous Registration - Hladovec, J (Thrombosis and Haemostasis, 1971)
The author describes a method of experimental arterial thrombosis in rats suitable for testing drugs with suggested antithrombotic effects. The thrombosis was provoked by electric current in the carotid artery and continuously registered by a contact thermometer.